BUKAN HANYA KANCA WINGKING PUSPA KARIMA DALAM STIGMA GENDER MENUJU PANGGUNG INTERNASIONAL - Mukhlis Anton Nugroho; Sunarmi; Santosa Soewarlan (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2023)
The rapid development of the digital era has changed the view of women's roles that were previously confined to household responsibilities, and now the stigma is starting to erode. In Javanese culture, there is the concept of